Effects of Cadmium on Root Morpho-Physiology of Durum Wheat - Sabella, Erika; Aprile, Alessio; Tenuzzo, Bernadetta Anna; Carata, Elisabetta; Panzarini, Elisa; Luvisi, Andrea; De Bellis, Luigi; Vergine, Marzia (Frontiers in Plant Science, 2022)
Durum wheat [Triticum turgidum L. subsp. durum (Desf.) Husn.] can accumulate a high level of Cd in grains with a significant variability depending on cultivars. Understanding how this toxic element is distributed in cereal tissues and grains is essential to improve the nutritional quality of cereal-based products. The main objective of this work was to investigate roots of durum wheat plants (cv. Iride) exposed to different Cd concentrations (0.5 and 5.0 μM) to identify the mechanisms involved in Cd management. Results showed that the root morphology was altered by Cd treatment both at macroscopic (increased number of tips and primary root length) and ultrastructural levels (cell membrane system damaged, cell walls thickened and enriched in suberin). On the other side, Cd was localized in vesicles and in cell walls, and the metal colocalized with the phytosiderophore nicotianamine (NA). Overall, data suggest that Cd is chelated by NA and then compartmentalized, through vesicular trafficking, in the root thickened walls reducing Cd translocation to the aerial organs of the plant.